Singular Solutions in Plasticity - Alexandrov, Sergei (SpringerBriefs in Continuum Mechanics,, 2018)
This book deals with singular solutions that appear in the vicinity of maximum friction surfaces for several rigid plastic models. In particular, it discusses precise asymptotic expansions as a necessary ingredient for the development of efficient numerical methods to solve boundary value problems that involve the maximum friction law as a boundary condition. An applied aspect of the singular solutions considered is that these solutions are capable of predicting the development of narrow hard layers near frictional interfaces in manufacturing processes.